2017
DOI: 10.2147/dmso.s150914
|View full text |Cite
|
Sign up to set email alerts
|

Visceral-to-subcutaneous fat ratio as a predictor of the multiple metabolic risk factors for subjects with normal waist circumference in Korea

Abstract: PurposeVisceral obesity has been recognized as a predictor of metabolic risk factors. However, few studies have evaluated the metabolic risks in subjects with normal waist circumference (WC). We aimed to examine if the visceral-to-subcutaneous fat ratio (VSR) has diagnostic value to identify multiple metabolic risk factors in subjects with normal WC, compared with visceral fat area (VFA) and subcutaneous fat area (SFA).MethodsThis is a cross-sectional study in which we have compared mean VFA, SFA, and VSR acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 31 publications
3
46
1
Order By: Relevance
“…These results were different with other research that found that higher BMI, WHR and total body fat had a strong association with hypertension in mining workers (6,17). The difference of the findings because in our study we are different condition in workers, characteristics of body composition, or there were other better indicator such as the research of Oh et al (18) in Korea that found other indicators that could predict hypertension and other metabolic risk factors better in normal waist circumference called visceral-to-subcutaneous fat ratio (VSR). There was also, hypertension strongly affected by another risk factors such as nutrition intake especially sodium intake had higher impact to blood pressure than another risk factors because more than half of Indonesian people (52.7%) are categorized as high sodium intake as described as sodium intake >2000mg/day (19).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results were different with other research that found that higher BMI, WHR and total body fat had a strong association with hypertension in mining workers (6,17). The difference of the findings because in our study we are different condition in workers, characteristics of body composition, or there were other better indicator such as the research of Oh et al (18) in Korea that found other indicators that could predict hypertension and other metabolic risk factors better in normal waist circumference called visceral-to-subcutaneous fat ratio (VSR). There was also, hypertension strongly affected by another risk factors such as nutrition intake especially sodium intake had higher impact to blood pressure than another risk factors because more than half of Indonesian people (52.7%) are categorized as high sodium intake as described as sodium intake >2000mg/day (19).…”
Section: Discussioncontrasting
confidence: 99%
“…After continued to multivariate analysis, visceral fat was found as the strongest predictor of hypertension in workers. These findings were similar to another study that also found that visceral fat consistently impacts to hypertension (10,18). We can conclude that among workers in this study, visceral fat was the independent determinant of hypertension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides the overall obesity, the anatomical location of fat also matters in disease development. Studies have shown that intra-abdominal visceral fat is strongly positively correlated with obesity-related diseases, while peripheral subcutaneous fat seems to have no effect or even a protective effect against developing metabolic syndrome [6][7][8][9][10] . However, the biological and genetic differences between visceral and subcutaneous fat are poorly understood.…”
mentioning
confidence: 99%
“…More specifically, the accumulation of adipose tissue in the visceral regions (intra-body cavity and near vital organs) is associated with an elevated risk of diabetes [3] and cardiovascular disease [4] , while subcutaneous lipid storage (within depots just under the skin) is comparatively benign [5,6] . Indeed, the visceral-to-subcutaneous adiposity ratio has been proposed as a predictor of metabolic health [7,8] and a study of obese individuals that transitioned from metabolically healthy to unhealthy obesity showed a corresponding increase in visceral fat [9] . Evidence has begun to accumulate suggesting that adipogenesis--differentiation of new fat cells--within subcutaneous depots is a key factor in modulating healthy versus unhealthy adipose tissue deposition.…”
Section: Introductionmentioning
confidence: 99%